Staphylococcus aureus and topical fusidic acid use: results of a clinical audit on antimicrobial resistance. (22nd February 2013) - Heng, Yee Kiat; Tan, Kian Teo; Sen, Priya; Chow, Angela; Leo, Yee Sin; Lye, David C.; Chan, Roy K.W.
Abstract Background Fusidic acid (FA) resistance in Staphylococcus aureus poses a problem for treating systemic methicillin‐resistant S. aureus infection, in which FA may otherwise remain a viable option. It can also result in treatment failure of common dermatological conditions such as impetigo and infected atopic eczema. Several studies have linked trends in prescribing medication and topical use of FA to development of resistance. However, few case–control studies have evaluated risk factors for developing FA resistance in S. aureus. Methods A clinical audit for antimicrobial resistance was performed in dermatology patients from the National Skin Centre who were admitted for inpatient care from 2006 to 2008 and had positive bacterial cultures for S. aureus. Each FA‐resistant S. aureus (FRSA) case was compared with four randomly selected FA‐susceptible (FSSA) cases. Medical records were reviewed retrospectively, and potential risk factors for development of resistance were analyzed. Results Thirteen of 37 patients with FRSA (35.1%) had used FA topically compared with 11 of 148 patients with FSSA (7.4%). Findings from multivariate analysis indicate that previous use of topical FA was the only independent risk factor of FA resistance (adjusted OR 7.46, 95% CI [2.60–21.41], P < 0.001). Patients' coexisting illnesses, recent hospitalization, or systemic antibiotic use were not significant risks. Conclusions Previous recent topical FA use correlated positively with FA resistance in S. aureus. Prescribing physicians must be vigilant of the rise of FA resistance and its resultant problems and prescribe topical FA discerningly.